(untitled) (Journal on studies and research of academic knowledge, 2018)
This research called “The Legal Framework that Sustains the Inclusion in Higher Education of Paraguay Demand Changes”; has as general objectives; To conclude on the imperative of introducing changes in the Legal Aspect, regarding Inclusion in Higher Education; and Propose the axes for the change in the Legislation, related to Inclusion in Higher Education. And as specific objectives; Describe the way Inclusion in Higher Education in Paraguay is considered; explain the way in which Inclusion in Higher Education of Comparative Law is considered and Determine the axes on Inclusion that present gaps of legal deficiency. An investigation was carried out, with a Qualitative approach, its scope was Analytical - Descriptive. The exhaustive analysis of the found theories was carried out; the analysis and interpretation of the Constitution of the Republic of Paraguay, with regard to Inclusion; the analysis of laws - Statutes, Treaties and International Agreements, which consider the topics of Inclusive Education. The most relevant results show that inclusion is considered from the highest legal standards, however it is still a distant reality, so that it is fully met, by different factors of all kinds, but that the failure is not only in the lack of adequate infrastructure; but in the mental openness of each human being, which will progressively be realized. Among the recommendations can be named the need to carry out the necessary reforms, in the current legislation, in order to implement positively and effectively Inclusion in Higher Education; Adequacy of the statutes of the Public Universities, in a very precise and viable manner; that families join forces to fight for equality of conditions.